Significance of the spatial reconstruction based on mathematical modeling in the surgical treatment of giant intracranial aneurysms - Nikolić Igor M.; Nagulić Mirjana; Antunović Vaso (Vojnosanitetski Pregled)
Background. The use of computer models for the 3- dimensional reconstruction could be a reliable method to overcome technical imperfections of diagnostic procedures for the microsurgical operation of giant intracranial aneurysms. Case report. We presented a case of successfully operated 52-year-old woman with giant intracranial aneurysm, in which the computer 3-dimensional reconstruction of blood vessels and the aneurysmal neck had been decisive for making the diagnosis. The model for 3- dimensional reconstruction of blood vessels was based on the two 2-dimensional projections of the conventional angiography. Standard neuroradiologic diagnostic procedures showed a giant aneurysm on the left middle cerebral artery, but the conventional subtraction and CT angiography did not reveal enough information. By the use of a personal computer, we performed a 3-dimensional spatial reconstruction of the left carotid artery to visualize the neck of aneurysm and its supplying blood vessels. Conclusion. The 3-dimensional spatial reconstruction of the cerebral vessels of a giant aneurysm based on the conventional angiography could be useful for planning the surgical procedure.